PREPARATION AND CHARACTERIZATION OF A QUERCETIN-TETRAETHYL ETHER-BASED PHOTOPROTECTIVE NANOEMULSION - Marlucy da Cruz Gonçalves; Viviane Martins R. dos Santos; Jason Guy Taylor; Fernanda Barçante Perasoli; Orlando David H. dos Santos; Ana Carolina S. Rabelo; Joamyr Victor Rossoni Junior; Daniela Caldeira Costa; Thiago Cazati (Química Nova)
Although Quercetin absorbs in the UVA/UVB electromagnetic region, it is limited for applications as a UV filter due to its low lipophilicity and capacity to penetrate the epidermis. In order to overcome this limitation, we synthetized and evaluated the photo protective properties of a derivative obtained from Quercetin. The derivative was prepared by alkylation of Quercetin with iodoethane and characterized by IR and NMR spectroscopy. The in vitro Solar Protection Factor was determined by the Mansur method and the cytotoxicity was evaluated using hepatocellular cell (Hep G2) cells. Finally, Quercetin and the corresponding derivative were incorporated in nanoemulsions. Nanoemulsions with particles sizes between 53 and 73 nm were obtained, and polydispersity indexes were around 0.1, indicating good homogeneity of the nanoemulsion particles. The cell viability study for the Quercetin derivative indicated a very low cytotoxicity profile. The chemical modification of Quercetin resulted in a promising compound with improved properties desirable for skin penetration and incorporation into sunscreen formulations.